Implementation of a Quality Management System based on ISO9001:2008 and its importance on culture collections - Simões, Marta Filipa Jesus Freitas (2013)
Culture collections (CC), in order to contribute to a better and sounder preservation of microbial biodiversity, constantly evaluate and analyse methodologies and are faced with the increasingly need to implement and maintain quality control [2]. Micoteca da Universidade do Minho (MUM) is a filamentous fungi culture collection established in May 1996, hosted by the Biological Engineering Centre, which is a centre of excellence integrated in the Institute for Biotechnology and Bioengineering (IBB). MUM has found with the implementation of a Quality Management System (QMS), based on the standard ISO 9001:2008, a way to contribute to this continuous search of a better Quality [1]. The implementation of the QMS occurred for almost 1 year during which 3 main steps were developed. The first step was the planning of the QMS, followed by the design of the system and documental development and the third step was the implementation of the QMS with the achievement of the certification in May 2011, from the independent assessment agency (Portuguese Association for Certification - APCER with the International Certification Network - IQNet). From this date on MUM has kept on performing QMS revision and pursuing a continuous improvement. From the analysis of the data, existing since the QMS implementation, it was possible to conclude that, when comparing the first year with the second year of the System, there was an increase on the demand of services supplied, noted through the increase on the number of customers that request the service of supply and number of strains requested. MUM, is a specialised CC that keeps on gaining recognition from other Session 15: Biological resource centers: quality management systems entities and acknowledgement of its services proving that the implementation of a QMS is an asset that should set an example to other CCs.